Special issue: Optical Characterizations of Novel Composite and Optically Active Materials. Editorial - Perova, Tatiana (My University, 2020)
Market pressures have placed new demands on modern photonic and opto-electronic materials, including requirements for miniaturization, higher efficiency, tunable and controllable optical and electrical properties, and consistent performance. These demands have resulted in the design and development of a wide range of new composite materials based on nanostructures of various shapes (quantum dots, quantum wires, quantum plates) as well as on layered structures of different dimensionality (viz. one-dimensional (1D), two-dimensional (2D), and three-dimensional (2D) structures). Concurrently, the optical properties of metals and their nanoparticles attract attention due to the rapid development of plasmonics, a new and promising field of applied physics and nanotechnology. Applications of metal nanoparticles and their composites include medical diagnostics and therapeutics, drug delivery, extreme UV lasers, manipulation of light for photovoltaics, and solar energy technologies, to name but a few. The Special Issue “Optical Characterizations of Novel Composite and Optically Active Materials” was launched to cover the latest advances in the development of novel composite materials with unique optical properties and their characterization using UV-VIS, CD, infrared, and Raman spectroscopy as well as numerical simulations. The eleven articles included in the Issue touch on different aspects of the fabrication and characterization of novel composite and nanostructured materials.
Keywords: Nanoscience & Materials; Education